Historia de la lectura En el mundo occidental - CAVALLO, Guglielmo dir (TAURUS, 1998)
Colb. : BONFIL, R.; GILMONT, J.F.; GRAFTON, A.; HAMESSE, J.; JULIA, D.; LYONS, M.; PARKES, M.; PETRUCCI,A.; SAENGER, P; SVENBRO, J.; WITTMANN, R.